Integrating Ecosystem Services Into Assessments of Sustainable Development Goals: A Case Study of the Beijing-Tianjin-Hebei Region, China - Hu, Siwei; Yang, Yanying; Li, Ang; Liu, Kai; Mi, Changhong; Shi, Rongguang (Frontiers in Environmental Science, 2022)
Trade-offs between eco-environment protection and socioeconomic development hinder the success of sustainable development goals (SDGs). Solutions based on ecosystem services (ESs) provide the co-benefits and pathways for fulfilling the SDGs. Assessing the progress towards SDGs based on the contribution of ESs to SDGs is crucial. Here, we assessed the spatial-temporal changes of ecosystem service values (ESV) and the SDG scores in the Beijing-Tianjin-Hebei Region (BTH) over the past 20 years using “ES-SDG linkages”. The total ESV and SDG Index score in the BTH showed a spatial pattern of high values in the northern plateau and low values in the southern plain. The total ESV increased from 25,335 yuan ha-1 in 2000 to 27,344 yuan ha-1 in 2020, and the improvement of ESV was mainly attributed to water provision and water regulation. However, the SDG Index score decreased slightly from 36.8 in 2000 to 35.5 in 2010, and then increased to 36.0 in 2020. SDG1, SDG12, and SDG15 performed best, whereas SDG6 and SDG11 performed poorly. Our study indicates that the changes of SDG Index score mainly depended on food provision, water provision, climate regulation, nutrient cycling, habitat & biodiversity, and cultural services. The assessment of SDGs suggests that SDG7 and SDG12 should be prioritized to advance the synergistic development of SDGs in the BTH, which will also enhance the understanding of stakeholders about the progress of achieving SDGs.